National Spatial Planning and the Constraints pertaining to the New Territorial Governance in Post-Revolutionary Tunisia - Mourad Ben Jelloul (L’Année du Maghreb)
Because of the January 2011 popular uprisings the local populations and the civil society in underprivileged areas exerted political pressure on the successive governments as well as the ruling political parties to improve the socio-economic situation of their regions and to end their isolation. And in order to reduce territorial inequity public authorities committed themselves on the one hand to major projects in the field of infrastructure and large-scale public facilities, on the other hand to deep-reaching institutional and legislative reforms namely by issuing and adopting the new Local Authorities Code and Urban Planning Code. Indeed, the analysis of the reconfiguration of territorial policies in Tunisia after 2011 is likely to allow us to highlight the difficulty of shifting from a highly centralized model to one that takes into consideration local authority players and citizen participation. This examination of territorial policies on various scales ( the study of territorial development policies and the various projects of statutory texts associated to them) will enable us in the first place to identify the dysfunctioning in the activities of the various authorities involved in the territorial reform, secondly to pinpoint the inconsistencies of their activities and ultimately to reconsider the ongoing of public activities and the change-resisting phenomena that impede the implementation of the new territorial governance policies.